2018
DOI: 10.4066/biomedicalresearch.29-17-2646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for factor five Leiden detection in patients with thromboembolism

Abstract: Introduction: Factor five Leiden is one of the most important hereditary risk factors for thrombotic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In a study conducted in Iran by Ghorbani et al, in 2018 that showed 100% compatible results for APCR screening result and PCR. 1 This same study was conducted after exclusion of history of anticoagulant drugs which showed that the very same patients who had Positive APCR results also had positive PCR results with 100% compatibility. In their study there are 26.7% cases which are positive for heterozygous mutation and 8.9% cases are homozygous, 1 that is much greater than our study in which there are 41 (97.61%) heterozygous cases and 1 (2.3%) homozygous cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study conducted in Iran by Ghorbani et al, in 2018 that showed 100% compatible results for APCR screening result and PCR. 1 This same study was conducted after exclusion of history of anticoagulant drugs which showed that the very same patients who had Positive APCR results also had positive PCR results with 100% compatibility. In their study there are 26.7% cases which are positive for heterozygous mutation and 8.9% cases are homozygous, 1 that is much greater than our study in which there are 41 (97.61%) heterozygous cases and 1 (2.3%) homozygous cases.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence have been found to 2.5% in Asians and 1.9% in Saudi Arabs respectively. 1 Laboratory tests can be screening and diagnostic assays. The screening tests are used to screen for the presence or absence of disease, while the diagnostic tests provide confirmatory evidence of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most DVT patients exhibit clinically subtle signs and symptoms, the symptoms may be noticeable depending on vascular in ammation and obstruction level. We should consider FVL-detecting tests in DVT patients because FVL mutation is one of the most prevalent reasons for thrombophilia, especially in young and pregnant women [4]. We present a case of recurrent Thromboembolism leading to chronic hypertension and cor-pulmonale due to Factor V Leiden mutation.…”
Section: Introductionmentioning
confidence: 95%